The Effect of H2SO4 Variations on the Synthesis and Characterization of Nanocellulose Using Pineapple Peel Fiber - Sitohang, Rosanti; Manurung, Posman; Suciyati, Sri Wahyu; Karo, Pulung Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Manufacturing nanocellulose made from pineapple peel fiber has been carried out using acid hydrolysis. This study aims to determine the effect of variations in H2SO4 on the synthesis of nanocellulose in pineapple peel fibers and on the crystal structure, surface morphology, and constituent elements of pineapple skin fiber nanocellulose. The variations of H2SO4 used were 5, 10, 15 and 20%. X-ray diffraction (XRD) and Scanning Electron microscopy (SEM) are characterizations used. The results of XRD characterization showed that the size of the resulting crystallite had met the appropriate size in the range of values from 2.03 – 2.21 nm. The results of SEM characterization show that the image is not porous and lumpy.